Muslim-Friendly Tourism as the Implementation of Maqasid al-Shari’ah in the Perspective of the Qur’an: A Systematic Literature Review - Isnaini Harahap; Marliyah; Muhammad Habibi Siregar; Waizul Qarni; Esma Cetin; Arifin, Rahman (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
This study explores Muslim-friendly tourism as an implementation of Maqāṣid al-Sharī‘ah from the perspective of the Qur’an through a Systematic Literature Review (SLR) approach. The research aims to identify how Islamic principles—particularly the five essential objectives of Sharia (ḥifẓ al-dīn, ḥifẓ al-nafs, ḥifẓ al-‘aql, ḥifẓ al-nasl, and ḥifẓ al-mal)—are integrated within the concept and practice of Muslim-friendly tourism. A systematic review of relevant journal articles published between 2020 and 2025 was conducted using thematic analysis to classify findings according to the Qur’anic and Maqāṣid frameworks. The results show that most studies on Muslim-friendly tourism emphasize economic and managerial aspects, such as market potential, halal certification, and destination branding, while limited attention is given to the Qur’anic and theological foundations. The analysis of Qur’anic verses, particularly those containing the command sīrū fī al-arḍ (“travel through the earth”), reveals that travel in Islam is not merely recreational but also spiritual, educational, and reflective—encouraging the appreciation of Allah’s creation and moral introspection. This study concludes that the concept of Muslim-friendly tourism can serve as a means of realizing the objectives of Sharia by preserving religion, life, intellect, lineage, and wealth, while fostering ethical, spiritual, and sustainable travel practices aligned with Islamic values.